Randomized clinical trial of the use of glyceryl trinitrate patches to aid arteriovenous fistula maturation. Issue 10 (29th July 2016) - Field, M.; McGrogan, D.; Marie, Y.; Joinson, M.; Andujar, C.; Dutton, M.; Krishnan, H.; Hodson, J.; van Dellen, D.; Inston, N. G.
Abstract: Background: Arteriovenous fistulas are critical for haemodialysis, but maturation rates remain poor. Experimental and anecdotal evidence has supported the use of transdermal glyceryl trinitrate (GTN) patches. The aim of this RCT was to determine whether use of a GTN patch aids arteriovenous fistula maturation. Methods: Patients referred for arteriovenous fistula formation were eligible. The GTN or placebo patch was applied immediately after surgery and left in situ for 24 h. The primary outcome measure was the change in venous diameter at 6 weeks after fistula formation. The secondary outcome measure was clinical fistula patency at 6 weeks. Results: Of 200 patients recruited (533 screened), 101 were randomized to the placebo group and 99 to the GTN group. Of these, 81 and 86 respectively completed surgery, and had follow‐up data available at 6 weeks. Improvements in venous diameter were similar in the two groups: mean(s.d.) increase 2·3(1·9) mm in the placebo group compared with 2·2(1·8) mm in the GTN group ( P = 0·704). The fistula failure rate did not differ significantly between the two groups: 23 per cent for placebo and 28 per cent for GTN ( P = 0·596). Conclusion: GTN transdermal patches used for 24 h after surgery did not improve arteriovenous fistula maturation. Registration number: NCT01685710 (http://www.clinicaltrials.gov ). Abstract : Ineffective